Drug-induced tumor-specific cytotoxicity in a whole tissue ex vivo model of human pancreatic ductal adenocarcinoma - Moro, Carlos Fernández; Selvam, Arun Kumar; Ghaderi, Mehran; Pimenoff, Ville N.; Gerling, Marco; Bozóky, Béla; Elduayen, Soledad Pouso; Dillner, Joakim; Björnstedt, Mikael (Frontiers in Oncology, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is the most common type of pancreatic cancer. PDAC has a dismal prognosis and an inherent resistance to cytostatic drugs. The lack of reliable experimental models is a severe limitation for drug development targeting PDAC. We have employed a whole tissue ex vivo culture model to explore the effect of redox-modulation by sodium selenite on the viability and growth of PDAC. Drug-resistant tumors are more vulnerable to redox-active selenium compounds because of high metabolic activity and redox imbalance. Sodium selenite efficiently and specifically reduced PDAC cell viability (p <0.02) (n=8) and decreased viable de novo tumor cell outgrowth (p<0.05) while preserving non-neoplastic tissues. Major cellular responses (damaged tumor cells > 90%, tumor regression grades III-IV according to Evans) were observed for sodium selenite concentrations between 15-30 µM. Moreover, selenium levels used in this study were significantly below the previously reported maximum tolerated dose for humans. Transcriptome data analysis revealed decreased expression of genes known to drive PDAC growth and metastatic potential (CEMIP, DDR2, PLOD2, P4HA1) while the cell death-inducing genes (ATF3, ACHE) were significantly upregulated (p<0.0001). In conclusion, we report that sodium selenite has an extraordinary efficacy and specificity against drug-resistant pancreatic cancer in an organotypic slice culture model. Our ex vivo organotypic tissue slice culture model can be used to test a variety of drug candidates for swift and reliable drug responses to individual PDAC cases.